Knowledge of cardiopulmonary resuscitation among Greek physiotherapists - Garyfallia Pepera; Εfstratios Xanthos; Andreas Lilios; Theodoros Xanthos (Monaldi Archives for Chest Disease, 2019)
High quality cardiopulmonary resuscitation (CPR) is crucial for influencing survival from cardiac arrest. Healthcare professionals are expected to know how to perform CPR as they may encounter emergency situations during their work. Physiotherapists, who use exercise as a therapeutic approach, should have good knowledge and skills in CPR not only to cope with possible adverse cardiac events during exercise but also because a widespread CPR application and early defibrillation can greatly reduce mortality due to heart attack. The aim of this study is to investigate knowledge of Greek physiotherapists in European Resuscitation Council guidelines for resuscitation. A secondary aim of this study was to assess and compare the knowledge score between those with and without previous training and/or lower self-confidence in CPR skills. Three hundred and fifty Greek physiotherapists who were working in hospitals and rehabilitation centres (face-to-face and e-mail contact) were randomly selected to complete an anonymous questionnaire containing demographic questions, CPR experience questions, and ten theoretical knowledge questions, based on European Resuscitation Council guidelines for resuscitation. The response ratio was 63% (n=220 physiotherapists). Respondents’ total mean score for the theoretic knowledge questions was 4.1±2 (range 1-10); 21.4% of the respondents had participated in a CPR course, while only 0.9% had previous experience in CPR performance. The group of respondents who had attended a CPR course had a significantly higher score in CPR knowledge questions and higher confidence score (p<0.01). Moreover, the physiotherapists who attended refresher courses in CPR in the workplace scored significantly higher (p<0.01). Our results indicate that Greek physiotherapists have knowledge gaps in the European Resuscitation Council guidelines for resuscitation. The percentage of Greek physiotherapists who had CPR certification and recertification was low, thus the CPR training should be mandatory for all working physiotherapists.